2019
DOI: 10.1016/s0140-6736(19)31053-0
|View full text |Cite|
|
Sign up to set email alerts
|

Extending thrombolysis to 4·5–9 h and wake-up stroke using perfusion imaging: a systematic review and meta-analysis of individual patient data

Abstract: Background Stroke thrombolysis with alteplase is currently recommended 0-4•5 h after stroke onset. We aimed to determine whether perfusion imaging can identify patients with salvageable brain tissue with symptoms 4•5 h or more from stroke onset or with symptoms on waking who might benefit from thrombolysis.Methods In this systematic review and meta-analysis of individual patient data, we searched PubMed for randomised trials published in English between Jan 1, 2006, and March 1, 2019. We also reviewed the refe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
250
1
18

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 379 publications
(292 citation statements)
references
References 24 publications
6
250
1
18
Order By: Relevance
“…No differences were observed in the mRS distribution analysis, but a higher proportion of alteplase-treated patients had major early neurological improvement, attained independent recovery (mRS 0-2 at day 90), and had imaging evidence of recanalization and reperfusion at 24h. As expected, alteplase-treated patients had an excess of symptomatic intracranial hemorrhage (6.2% vs. 0.9%) EXTEND, 10 and an individual patient data pooled analysis of EXTEND, ECASS-4 and EPITHET, 21 provide further evidence supporting the concept that tissue viability on physiological imaging should be used for reperfusion therapy selection beyond the 4.5 h window or when onset time is uncertain, adding to 1021 evidence from WAKE-UP, 11 DAWN 14 and DEFUSE-3. 15 .…”
supporting
confidence: 69%
“…No differences were observed in the mRS distribution analysis, but a higher proportion of alteplase-treated patients had major early neurological improvement, attained independent recovery (mRS 0-2 at day 90), and had imaging evidence of recanalization and reperfusion at 24h. As expected, alteplase-treated patients had an excess of symptomatic intracranial hemorrhage (6.2% vs. 0.9%) EXTEND, 10 and an individual patient data pooled analysis of EXTEND, ECASS-4 and EPITHET, 21 provide further evidence supporting the concept that tissue viability on physiological imaging should be used for reperfusion therapy selection beyond the 4.5 h window or when onset time is uncertain, adding to 1021 evidence from WAKE-UP, 11 DAWN 14 and DEFUSE-3. 15 .…”
supporting
confidence: 69%
“…However, as shown in clinical studies, treatment with tPA is only effective if administered within 4.5 hours postischemia. Although it was recently reported that the timeframe for effective thrombolysis treatment extends up to 9 hours after the onset of a stroke, this time window remains narrow [5][6][7], not to mention the side effects of tPA, which include enhanced risk of brain hemorrhage. In fact, the number of patients actually benefiting from tPA is very limited (2-5%) [16].…”
Section: Current Barriers and Strategies To Treat Strokementioning
confidence: 99%
“…Thus, this disease has become an enormous threat to human health and a huge burden to the healthcare system worldwide [1][2][3][4]. So far, the only FDA-approved medication for ischemic stroke is the tissue plasminogen activator (tPA) when applied within 3 hours of an acute ischemic stroke attack, which therefore benefits only a small portion of the patients (2-5%) [5][6][7]. A great deal of effort has been made toward developing neuroprotectants, which mostly aim to block individual cytotoxic pathways in the early stages of stroke pathogenesis.…”
Section: Introductionmentioning
confidence: 99%
“…More recent trials have extended the time windows for such therapies, which may eventually lead to more pediatric patients being considered eligible for treatment. [5][6][7] The relative plasticity of a child's brain, however, may offer significant possibilities for targeting the recovery phase after stroke with a much larger window of opportunity for intervention.…”
Section: What Toll Does Pediatric Stroke Take?mentioning
confidence: 99%